Ñausa urpi: the Symbol as a Figurative Resource in the Composition of Quechua Songs in the Narrative of José María Arguedas - Altamirano Flores, Federico (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The transcultural and polyphonic narrative of José María Arguedas is imbued with Quechua songs, which are structured through canonical rhetorical figures established by the aesthetics of Quechua culture. The aim of the article is to explain the use of the symbol as a central literary figure in the composition of the Quechua songs embedded in Arguedas’ narrative. The selected textual corpus consists of Quechua resistance songs. To identify and explain these symbols, cultural rhetoric has been used as a hermeneutic tool, proposed by Tomás Albaladejo, as it allows the discovery of the mechanisms of the rhetorical organization of lyrical discourse. The results of the study show that, indeed, the songs are configured around recurring symbols such as the bull, the butterfly, the dove, the tree, and the river. The contribution of the study lies in the explanation of the process of interdiscursive construction of the symbol in the Quechua songs.